Evidence-based lifestyle interventions in the workplace—an overview. (26th November 2013) - Schröer, S.; Haupt, J.; Pieper, C.
Abstract : Background: Lifestyle-related health issues affect the economic position of organizations and contribute to reduced productivity, increased absenteeism and health care costs. Aims: To summarize the effectiveness of different workplace health interventions for promoting healthy lifestyle, preventing diseases and reducing health care costs. Methods: We searched MEDLINE via Pubmed, EMBASE, Cochrane Library, NelH, HighWire Press and Google Scholar in March 2012. Systematic reviews and meta-analyses of workplace interventions aimed at promoting physical activity, healthy weight and good nutrition were included. Three authors assessed the quality of the reviews and extracted data on methods, interventions, outcomes, results and effect sizes. Results: We identified 15 publications covering a total of 379 original studies. Three systematic reviews found beneficial effects of workplace nutrition interventions on employees' dietary behaviour. Three reviews found multi-component physical activity interventions to be effective in increasing employees' physical activity and fitness. The other activity promotion interventions were less effective regarding physical activity and weight-related outcomes. In terms of weight management, our findings favour multi-component interventions that focus on both physical activity and nutrition over single dietary programmes. Conclusions: Workplace health promotion interventions may improve physical activity, dietary behaviour and healthy weight. There is no evidence of increased efficacy associated with specific intervention types. Workplace health promotion should focus on either physical activity or weight or nutrition behaviour to maximize effectiveness. Best evidence is available for multi-component interventions.